Iron at the Centre of Candida albicans Interactions - Fourie, Ruan; Kuloyo, Oluwasegun O.; Mochochoko, Bonang M.; Albertyn, Jacobus; Pohl, Carolina H. (Frontiers in Cellular and Infection Microbiology, 2018)
Iron is an absolute requirement for both the host and pathogens alike and is needed for normal cellular growth. The acquisition of iron by biological systems is regulated to circumvent toxicity of iron overload, as well as the growth deficits imposed by iron deficiency. In addition, hosts, such as humans, need to limit the availability of iron to pathogens. However, opportunistic pathogens such as Candida albicans are able to adapt to extremes of iron availability, such as the iron replete environment of the gastrointestinal tract and iron deficiency during systemic infection. Candida albicans has developed a complex and effective regulatory circuit for iron acquisition and storage to circumvent iron limitation within the human host. As C. albicans can form complex interactions with both commensal and pathogenic co-inhabitants, it can be speculated that iron may play an important role in these interactions. In this review, we highlight the regulation of iron homeostasis within the host as well as C. albicans. In addition, the review argues for the need for further research into the role of iron in polymicrobial interactions. Lastly, the role of iron in treatment of C. albicans infection is discussed.